Stk33 is required for spermatid differentiation and male fertility in mice - Martins, Leila; Lohmann, Ingrid; Fröhling, Stefan (Developmental biology, 2018)
Spermiogenesis is the final phase during sperm cell development in which round spermatids undergo dramatic morphological changes to generate spermatozoa. Here we report that the serine/threonine kinase Stk33 is essential for the differentiation of round spermatids into functional sperm cells and male fertility. Constitutive Stk33 deletion in mice results in severely malformed and immotile spermatozoa that are particularly characterized by disordered structural tail elements. Stk33 expression first appears in primary spermatocytes, and targeted deletion of Stk33 in these cells recapitulates the defects observed in constitutive knockout mice, confirming a germ cell-intrinsic function. Stk33 protein resides in the cytoplasm and partially co-localizes with the caudal end of the manchette, a transient structure that guides tail elongation, in elongating spermatids, and loss of Stk33 leads to the appearance of a tight, straight and elongated manchette. Together, these results identify Stk33 as an essential regulator of spermatid differentiation and male fertility.